2019
DOI: 10.1182/blood-2019-01-895086
|View full text |Cite
|
Sign up to set email alerts
|

CDK9 and mTOR: trading places

Abstract: In this issue of Blood, Beauchamp et al 1 reveal that the kinase CDK9, typically associated with transcriptional elongation, 2 directly modulates translation through coopting components of the major translational regulatory complex mammalian target of rapamycin (mTOR). 3,4 These studies represent a major shift from the current paradigm; specifically, this work demonstrates that other kinases can coopt mTOR cofactors in order to modulate not only translation but also transcription as well as positioning CDK9 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…CDK9 alongside mTOR complexes modulate translation. TOR complexes have recently emerged as a potential target for autophagic regulation[ 37 ]. This study confirmed that CDK9 is highly expressed in CRC and that expression of CDK9 is positively correlated with autophagy in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CDK9 alongside mTOR complexes modulate translation. TOR complexes have recently emerged as a potential target for autophagic regulation[ 37 ]. This study confirmed that CDK9 is highly expressed in CRC and that expression of CDK9 is positively correlated with autophagy in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Due to being a part of the major pathways responsible for the development of highly prevalent pathologies, such as cancer, CDK9 represents a new class of pharmaceutical targets. Although CDK9 traditionally acts in transcription elongation, recent studies revealed that it also interacts with a wide range of proteins involved in translation, RNA processing, translation termination, and epigenetic modifications [58,138,139]. Research efforts should continue to elucidate CDK9's functions to understand the higher-order mechanism responsible for the development of malignancies.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The mTOR pathway is involved in cell growth, proliferation, differentiation, apoptosis, and metabolism. [27,28] It is an important target for antitumor therapy because it controls many important aspects of the tumor process. [29,30] Placental development is characterized by extensive angiogenesis.…”
mentioning
confidence: 99%